2007
DOI: 10.1291/hypres.30.723
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Baroreflex Sensitivity: Association with Morning Blood Pressure

Abstract: Baroreflex sensitivity (BRS) is a primary mechanism for acute and chronic control of blood pressure (BP).However, there are few data showing the relationship between BRS and ambulatory BP (ABP). We assessed the hypothesis that BRS specifically contributes to some specific parameters of ABP in never-treated hypertensive/normotensive subjects. We studied 128 subjects (mean age: 54.5 ± 13 years, 60% male) consisting of 92 untreated hypertensive and 36 normotensive subjects. Radial tonometric BP and simultaneous R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 47 publications
4
9
0
Order By: Relevance
“…Although the maximum home SBP differs from BP variability in that it refers specifically to transient changes in BP, these 2 variables often have similar associations with other clinical indices, such as arterial stiffness and baroreceptor dysfunction. 1,24,25 In the present study, age and PWV, both of which may be involved in the impairment of the arterial baroreflex, 26,27 were independent determinants of the size of the maximum home SBP. Thus, a baroreceptor dysfunction could be potentially involved in the mechanisms of larger-value maximum home SBP.…”
Section: Discussionsupporting
confidence: 49%
“…Although the maximum home SBP differs from BP variability in that it refers specifically to transient changes in BP, these 2 variables often have similar associations with other clinical indices, such as arterial stiffness and baroreceptor dysfunction. 1,24,25 In the present study, age and PWV, both of which may be involved in the impairment of the arterial baroreflex, 26,27 were independent determinants of the size of the maximum home SBP. Thus, a baroreceptor dysfunction could be potentially involved in the mechanisms of larger-value maximum home SBP.…”
Section: Discussionsupporting
confidence: 49%
“…We felt it important to clearly delineate these mechanisms in otherwise healthy individuals to document the "normal" physiological response in the absence of any cofounding pathology and/or medications. Although the study of young healthy individuals is limited as far as generalizing the results to clinical populations, diurnal variation in baroreflex sensitivity is robust in hypertensive patients, 12,13 and our findings, therefore, bring to question whether better management of cardiovascular events may be achieved through interventions targeted specifically at the neural and/or mechanical components. The potential for the use of targeted therapy has been suggested in relation to sympathetic baroreflex function.…”
Section: Clinical Perspectivesmentioning
confidence: 80%
“…35 Studies using spontaneous baroreflex indices have consistently shown that the highest sensitivities occur during the night, with reduced sensitivities in the morning after waking. 10,12,13,33 However, the variations during the daytime have not been consistent between studies. For example, Tochikubo et al 12 found the circadian variation to be bimodal with a secondary peak in baroreflex sensitivity at 7:00 PM and trough at 11:00 PM.…”
Section: Comparison With Previous Studiesmentioning
confidence: 88%
“…Morning SBP has been shown to inversely correlate with baroreflex sensitivity (37) and to be a strong risk marker for stroke in elderly subjects (38). The morning SBP surge has also been reported as a predictor of cerebrovascular events (12,13).…”
Section: Discussionmentioning
confidence: 99%